2019
DOI: 10.9734/jalsi/2019/v22i130119
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-UV Standard Phenolic Constituents of African Bush Mango (Irvingia gabonensis) and Molecular Docking on Polyphenol Oxidases

Abstract: Introduction: Irvingia gabonensis belongs to the Irvingiaceae plant family and commonly known as the African bush mango, wild mango, Dika nut and Manguier sauvage. The fruits of I. gabonensis are edible and their use in traditional medicine has been reported for the treatment of diabetes, diarrhea, wound ulcer, hepatic disorder, microbial infections, and inflammatory pains.  Aim: This study aimed to identify the standard phenolic contents of I. gabonensis fruit pulp and peel extracts and investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Reduced mounting and intromission latencies in rats fed an ABM-supplemented diet may have aided in the initiation of sexual behavior, whereas increased intromission and mounting numbers in male rats may have improved copulatory efficiency, as shown in previous studies in which decreased mounting and intromission latencies were reported to be indicators of sex behavior [29]. Dietary supplementation with ABM appears to stimulate male sexual activity by increasing mounting and intromission counts and lowering mounting and intromission latencies, and it may be attributed to the presence of bioactive phenolic substances and its high arginine level previously reported [30,31].…”
Section: Discussionmentioning
confidence: 69%
“…Reduced mounting and intromission latencies in rats fed an ABM-supplemented diet may have aided in the initiation of sexual behavior, whereas increased intromission and mounting numbers in male rats may have improved copulatory efficiency, as shown in previous studies in which decreased mounting and intromission latencies were reported to be indicators of sex behavior [29]. Dietary supplementation with ABM appears to stimulate male sexual activity by increasing mounting and intromission counts and lowering mounting and intromission latencies, and it may be attributed to the presence of bioactive phenolic substances and its high arginine level previously reported [30,31].…”
Section: Discussionmentioning
confidence: 69%
“…Irvingia gabonensis belong to the species of African tree in the genus Irvingia of the Irvingiaceae plant family commonly known as wild mango, African mango, bush mango, or ugiri (Igbo) [4,5]. It has yellow fruits when ripe, and varies in size and shapes between varieties with fibrous pulp covering the seed [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the course of dehulling and crushing or making into powder, the color changes from whitish to greyish, making it appears dull, and eventually turns brown, thereby loses its acceptability for market value. Fruits, vegetables and seeds are susceptible to enzymatic browning, which is typically catalyzed by polyphenol oxidase (PPO) (Liu et al 2007;Guven et al 2017;Adeseko et al 2019). PPOs catalyse mono-and o-diphenol conversion to o-quinones during ripening, postharvest handling, storage and processing of fruits and seeds (Spagna et al 2005;Sélles-Marchart et al 2006).…”
Section: Introductionmentioning
confidence: 99%